Tectonics and metallogeny of the Khakandzha ore district in the Okhotsk–Chukotka volcanic belt; Russian Journal of Pacific Geology; Vol. 10, iss. 5 - Yushmanov Yu. P. Yury Petrovich (2016, 2016)
Title screen